Epidemiology of Diabetes and Atherosclerotic Cardiovascular Disease Among Asian American Adults: Implications, Management, and Future Directions: A Scientific Statement From the American Heart Association - Kwan, Tak W; Wong, Sally S; Hong, Yuling; Kanaya, Alka M; Khan, Sadiya S; Hayman, Laura L; Shah, Svati H; Welty, Francine K; Deedwania, Prakash C; Khaliq, Asma; Palaniappan, Latha P (Circulation (New York, N.Y.), 2023)
Asian American individuals make up the fastest growing racial and ethnic group in the United States. Despite the substantial variability that exists in type 2 diabetes and atherosclerotic cardiovascular disease risk among the different subgroups of Asian Americans, the current literature, when available, often fails to examine these subgroups individually. The purpose of this scientific statement is to summarize the latest disaggregated data, when possible, on Asian American demographics, prevalence, biological mechanisms, genetics, health behaviors, acculturation and lifestyle interventions, pharmacological therapy, complementary alternative interventions, and their impact on type 2 diabetes and atherosclerotic cardiovascular disease. On the basis of available evidence to date, we noted that the prevalences of type 2 diabetes and stroke mortality are higher in all Asian American subgroups compared with non-Hispanic White adults. Data also showed that atherosclerotic cardiovascular disease risk is highest among South Asian and Filipino adults but lowest among Chinese, Japanese, and Korean adults. This scientific statement discusses the biological pathway of type 2 diabetes and the possible role of genetics in type 2 diabetes and atherosclerotic cardiovascular disease among Asian American adults. Challenges to provide evidence-based recommendations included the limited data on Asian American adults in risk prediction models, national surveillance surveys, and clinical trials, leading to significant research disparities in this population. The large disparity within this population is a call for action to the public health and clinical health care community, for whom opportunities for the inclusion of the Asian American subgroups should be a priority. Future studies of atherosclerotic cardiovascular disease risk in Asian American adults need to be adequately powered, to incorporate multiple Asian ancestries, and to include multigenerational cohorts. With advances in epidemiology and data analysis and the availability of larger, representative cohorts, furthering refining the Pooled Cohort Equations, in addition to enhancers, would allow better risk estimation in segments of the population. Last, this scientific statement provides individual- and community-level intervention suggestions for health care professionals who interact with the Asian American population.